A case for Kvanvig's objectual understanding as the primary epistemic aim of education - Fungo, Joyce Estelle S. (Animo Repository, 2021)
What does a successful education entail for the epistemic life of learners? In the recent years, epistemic issues in education have made its way onto contemporary philosophical literature. A portion of this body of literature has been dedicated to addressing the debate about which of the epistemic goods ought to hold primacy in educational pursuits. This paper takes up the project of providing a viable solution to the problem of epistemic aims of education. It begins with a critical analysis of the existing solutions in the debate, with the intention of arguing for the need to develop a new position. The study analyses the positions of Alvin Goldman (1999), Harvey Siegel (2005), and Jason Baehr (2013), who vouch for truth, critical thinking, and intellectual virtues respectively as the primary aim of education. In arguing against these positions, the paper recommends an alternative position in the form of Jonathan Kvanvig’s (2003) notion of objectual understanding. The study further elaborates the specific features available in this epistemic state which allow for it to hold primacy over its other epistemic contenders. It highlights the epistemic value present in adhering to this position. In arguing for objectual understanding, the study also provides a defense of Kvanvig’s theory from problems and existing criticisms. It offers reasons for why his conception of understanding is the most suitable for the project. Finally, the study exposes how shifting the epistemological focus to understanding can influence other epistemic concepts in education. Ultimately, the study argues that objectual understanding ought to be the primary epistemic aim of education.